Genotype‐Phenotype Relations for the Parkinson's Disease Genes Parkin, PINK1, DJ1: MDSGene Systematic Review - Kasten, Meike; Hartmann, Corinna; Hampf, Jennie; Schaake, Susen; Westenberger, Ana; Vollstedt, Eva‐Juliane; Balck, Alexander; Domingo, Aloysius; Vulinovic, Franca; Dulovic, Marija; Zorn, Ingo; Madoev, Harutyun; et al. (Movement disorders, 2018)
This first comprehensive MDSGene review is devoted to the 3 autosomal recessive Parkinson's disease forms: PARK‐Parkin, PARK‐PINK1, and PARK‐DJ1. It followed MDSGene's standardized data extraction protocol and screened a total of 3652 citations and is based on fully curated phenotypic and genotypic data on >1100 patients with recessively inherited PD because of 221 different disease‐causing mutations in Parkin, PINK1, or DJ1. All these data are also available in an easily searchable online database (www.mdsgene.org), which also provides descriptive summary statistics on phenotypic and genetic data. Despite the high degree of missingness of phenotypic features and unsystematic reporting of genotype data in the original literature, the present review recapitulates many of the previously described findings including early onset (median age at onset of ∼30 years for carriers of at least 2 mutations in any of the 3 genes) of an overall clinically typical form of PD with excellent treatment response, dystonia and dyskinesia being relatively common and cognitive decline relatively uncommon. However, when comparing actual data with common expert knowledge in previously published reviews, we detected several discrepancies. We conclude that systematic reporting of phenotypes is a pressing need in light of increasingly available molecular genetic testing and the emergence of first gene‐specific therapies entering clinical trials. © 2018 International Parkinson and Movement Disorder Society